PT.X adalah perusahaan cat ANALISIS PENGENDALIAN KUALITAS PRODUK EMBER CAT TEMBOK 5KG MENGGUNAKAN METODE NEW SEVEN TOOLS (Studi Kasus: PT. X): (Studi Kasus: PT. X) - hari, Ari Zaqi Al Faritsy; Hengky Hari Prasetiyo (Lembaga Pengembangan Kinerja Dosen, 2022)
PT.X is a manufacturing company whose one product is Gallon Paint bucket 5kg. The problems faced by this company are factors that cause production defects, it is necessary to improve the quality of 5kg paint gallons. the flow of stages in the research using the New Seven Tools method with the stages, namely affinity diagrams, Affinity Diagrams, Relationship Diagrams, Tree diagrams, Matrix Diagrams, Data Analysis Matrix, Arrow Diagrams, Process Decision Program Charts. With the results of this study, it is known that the factors of the occurrence of production defects are the human factor The condition of the operator is sick, the operator is in a hurry, the lack of understanding of the production machine. Material factors Inappropriate mixing of raw materials. Machine Factors Short Machine Maintenance Time, Number of Machines That Are Not Operating, Lack of Spare Parts To Do Maintenance. Factors SOP method of Quality Standards that are not written in the production section. Environmental factors Hot Working Environment Temperature, Long Distance Between Production, Noisy Work Environment. The suggestion given to reduce this production defect is to give sick leave for 3 days. Adding operators to the Inject Molding machine at least 2. Providing training on the operation of the machine to each operator. Preparation of appropriate raw material mixture formulas. Placing unused machines in 1 warehouse room. Making regular and strict maintenance schedule for machine maintenance. Stocking spare parts in the Workshop room Providing understanding of product defect SOPs. Providing a fan in the room and increasing air ventilation. Updated the production line layout. Place the machine in a soundproof room and wear earplugs.